Inclusive Organizing through the Creative Economy: UNESCO Fortaleza Creative City of Design Project - Menezes, Rodrigo Ábnner Gonçalves; Ipiranga, Ana Sílvia Rocha (Organizações & Sociedade, 2025)
One of the main problematics that comes up when discussing cities in Brazil is how to reduce social inequalities for the development of inclusive cities among its margins. For this purpose, the membership of Fortaleza as a UNESCO Creative City of Design leads to the development of practices, analyzed in this study through the strategy-as-practice approach, in order to reduce social inequalities in the context of the organization of the city. This study raises as its main question: how does this project act in terms of strategies-as-practices and their effects on the organizing process for a more inclusive city? The objective of this article is to understand the strategy-as-practice of the UNESCO Fortaleza Creative City of Design Project and its effects on the creative organizing process for a more inclusive city. The research method chosen was Grounded Theory, which considers that the analysis is inseparable from the data collection stage. The results show that the UNESCO Fortaleza Creative City of Design Project was developed based on culturallydriven urban strategizing processes. It is evident that these processes were based on practices of co-creation among stakeholders embedded in a wide and diversified network of relationships. These processes influenced creative urban organizing aimed at a more inclusive city.